The voice of #SaveRajaAmpat: Digital movements against nickel mining - Thohir, Muhammad Aminullah (Environment Conflict, 2025)
Background: The movement to against nickel mining in Raja Ampat was raised in early July 2025. The movement began with a post from Greenpeace Indonesia who were kicked out by security personnels when they protested against nickel mining in Raja Ampat in the middle of an event attended by industry professionals, government officials, experts, and representatives from various countries. This resulted in the digital community joining in to voice their opposition to Raja Ampat with the hashtag #SaveRajaAmpat. This research presents the circumstances that led the digital community to engage in the #SaveRajaAmpat campaign on social media and examines the effectiveness of social media campaigns. Methods: Using qualitative methods with a netnographic approach. The author used secondary data from Greenpeace Indonesia, organizational documents, news articles, and posts by X accounts about Raja Ampat. Findings: The digital community against nickel mining in Raja Ampat due to environmental concerns; frustration and disappointment with the state, government & oligarchy; Solidarity with the Papuan people; a spirit of resistance towards capitalism and a desire for tourism & to enjoy the natural beauty of Raja Ampat. However, the movement on social media was short-lived and faded due to minor victories achieved through the revocation of several companies permits and distraction by other issues. Conclusion: Social movement through social media are less effective, therefore it is necessary to unite social media movements and direct action with the spirit of disappointment towards the state and a spirit of resistance against capitalism so that the movement can be sustained. Novelty/Originality of this article: This change explains the various motivations of the digital community to engage in activism and explains why digital movements are less effective.